The Spaces Between Fault/Lines: Collaborative Politics of Addiction in Japan. (September 2022) - Atici, Selim Gokce
In the last decade, the Japanese welfare system has dramatically expanded health-care services and introduced new therapeutic programs for people diagnosed with addiction problems. Staff and members of volunteer-led non-profit rehabilitation centers (known as DARCs) together with medical professionals, developed pilot clinical therapies and critical studies of current clinical models. By encouraging encounters between professionals and DARC volunteers, these programs serve as a basis for new social and economic welfare policies. They incorporate critical assessments of causality and responsibility in the context of social marginalization and the lack of medical care. Scholars of Japanese welfare and a wider scholarship of governmentality and drug policies have analyzed deinvestment in marginalized populations by focusing on medicalization and criminalization. However, the Japanese therapeutic expansion produced alternative experiential, moral, and medical understandings of drug use, as it enabled grassroots participation through new forms of citizenship, peer studies, and alliances across medical, penal, and welfare fields. This article therefore focuses on how grassroots activists engage with medical professionals and welfare officials through self-studies and research about these collectives. Drawing on the anthropology of addiction literature and critical drug studies, and 6 months of anthropological fieldwork in Japan, I interrogate the emerging collaborative politics of addiction in Japan, focusing on alliances between various actors and institutions, the organization of care in a time of economic abandonment of marginalized social classes, and the making of grassroots solidarity. Finally, I reflect on the politics of fault and practices of space-making that characterize these pragmatic alliances. I consider these alliances as interventions into the hegemonic understandings of fault and responsibility in the context of social assistance and addiction-specific welfare policies.